Analysis of Polarization Charge on III-V Compound Materials for HEMT Devices - Myint Aye, May Nwe; Than Htike Aung; Win Zaw Hein (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
The paper presents the polarization charge analysis on III-V compound materials for HEMT Devices. The mathematical model for polarization charge analysis is derived from the experimental outcomes from the laboratory. The electron density in the channel of HEMT devices and the current versus polarization charges are demonstrated based on the numerical analysis. According to the numerical results, the results could be proved to fabricate the real devices in practical applications. The numerical analyses could be carried out by using MATLAB language.